Regulatory T cells regulate blastemal proliferation during zebrafish caudal fin regeneration - Hui, Subhra P.; Sugimoto, Kotaro; Sheng, Delicia Z.; Kikuchi, Kazu (Frontiers in Immunology, 2022)
The adaptive immune system is conserved in highly regenerative animals such as urodele amphibians and teleost fish, but the role of T cells in appendage regeneration remains unclear. In this study, we revealed an important role for regulatory T cells (Tregs), a subset of T cells that regulate tolerance and tissue repair, in the epimorphic regeneration of zebrafish caudal fin tissue. Upon amputation, fin tissue-resident Tregs infiltrate into the blastema, a population of progenitor cells that produce new fin tissues. Conditional genetic ablation of Tregs attenuates blastemal cell proliferation during fin regeneration. Blastema-infiltrating Tregs upregulate the expression of igf2a and igf2b, and pharmacological activation of IGF signaling restores blastemal proliferation in Treg-ablated zebrafish. These findings further extend our understandings of Treg function in tissue regeneration and repair.